2009
DOI: 10.1016/j.marenvres.2008.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of benzo[a]pyrene on DNA damage and histological alterations in gonad of scallop Chlamys farreri

Abstract: To investigate the biological impact of polycyclic aromatic hydrocarbons (PAHs) on reproductive system, scallops Chlamys farreri were continuously exposed to benzo[a]pyrene (BaP) (0.5, 3, 10microgL(-1)) during 15 days. DNA damage and histological alterations were examined in female gonad. DNA strand break levels significantly increased after 12h exposure, and remained high and significantly different from control values until the end of the exposure. In the ovaries of the scallops exposed to 10microgL(-1) BaP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…In the present study, cumulative gonadal disorders were observed in male mussels concerning both tar exposure and accumulation of PAHs and metals. In molluscs, similar disorders have been related to PAHs and metals pollution in wild environments (Pridmore et al, 1990;Viarengo et al, 1990;Bolognesi et al, 1999;Alonso et al, 2001;Tay et al, 2003;Aarab et al, 2004;Smolders et al, 2004;Jing-Jing et al, 2009;Yurchenko and Vaschenko, 2010;Ortiz-Zarragoitia et al, 2011;Ruiz et al, FIGURE 8 | Multivariate analysis: cluster analysis overlayed to dbRDA based to the fitted model selected by Bray-Curtis similarity of chemicals accumulation, and biometric and morphometric variables from Mytilus galloprovincialis, exposed to different tar concentrations during 0, 10, and 17 days (subscripts). R, Reference mussels.…”
Section: Gonadal and Histological Disordersmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, cumulative gonadal disorders were observed in male mussels concerning both tar exposure and accumulation of PAHs and metals. In molluscs, similar disorders have been related to PAHs and metals pollution in wild environments (Pridmore et al, 1990;Viarengo et al, 1990;Bolognesi et al, 1999;Alonso et al, 2001;Tay et al, 2003;Aarab et al, 2004;Smolders et al, 2004;Jing-Jing et al, 2009;Yurchenko and Vaschenko, 2010;Ortiz-Zarragoitia et al, 2011;Ruiz et al, FIGURE 8 | Multivariate analysis: cluster analysis overlayed to dbRDA based to the fitted model selected by Bray-Curtis similarity of chemicals accumulation, and biometric and morphometric variables from Mytilus galloprovincialis, exposed to different tar concentrations during 0, 10, and 17 days (subscripts). R, Reference mussels.…”
Section: Gonadal and Histological Disordersmentioning
confidence: 99%
“…These pathologies result from direct binding of these chemicals and their metabolites to macromolecules and, secondarily, from toxicity of the reactive oxygen species generated in their biotransformation (Sokol, 1987;Mortelmans and Zeiger, 2000;Adhikari et al, 2001;Ercal et al, 2001;Wang and Shi, 2001;Boström et al, 2002;Pufulete et al, 2004;Flora et al, 2008;Ono et al, 2008;Veeramachaneni, 2008;Sanders et al, 2009;Swedenborg et al, 2009;Balabanič et al, 2011;Tchounwou et al, 2012). Also in marine invertebrates, mainly molluscs, there are studies showing reproductive and neoplastic disorders related to pollution (Viarengo et al, 1990;Bolognesi et al, 1999;Matozzo et al, 2001;Creasy and Foster, 2002;Au, 2004;Pichaud et al, 2008;Jing-Jing et al, 2009;Ji et al, 2011;Ruiz et al, 2011). However, in these, much remains unknown about their biotransformation and toxic mechanisms, and few studies have proved their causal relationship under laboratory conditions (Lavado et al, 2006;Ortiz-Zarragoitia and Cajaraville, 2006;Jing-Jing et al, 2009;Schäfer and Köhler, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Like many other bivalves, C. farreri is susceptible to environmental contaminants because of its sessile nature and filter-feeding behavior (Miao et al 2009;Liu et al 2012). The reproductive process controlled by steroids in bivalves has been shown to be interfered by endocrine-disrupting compounds (EDCs), which are widespread in aquatic environments Langston et al 2007;Porte et al 2006;Ketata et al 2008;Andrew et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Bivalves are particularly at risk to aquatic xenobiotic chemicals because they are stationary and filter relatively high volume of water, including suspended particles (Jing-Jing et al, 2009). C. farreri is the specific shellfish bivalve which has important commercial and ecological value in the northern coastal provinces of China, and it often has been used as a bioindicator in water pollution monitoring (Pan et al, 2008).…”
Section: Introductionmentioning
confidence: 99%